The Implementation of Delegated Authority Through an Integrated District Service System (Patent) - Zaini Ali; Sadu Wasistiono; Rossy Lambelanova; Muhammad Ilham (Universitas Muhammadiyah Ponorogo, 2026)
Districts hold a strategic position connecting regencies with villages and vice versa. Therefore, innovation in sub-district services through PATENT is a breakthrough in promoting sub-districts as community service centers. This study aims to determine and analyze the implementation of delegated authority by the Head of Sungai Mandau Sub-district, Siak Regency and Siak Hulu Sub-district, Kampar Regency, the factors that hinder the delegation of authority, the implications for implementing regional regulations, the performance of the sub-districts in the last 3 years, and the model of delegation of authority delegated to the sub-districts. Using a descriptive-explanatory qualitative approach, the study finds: First, delegative authority is being implemented well in Sungai Mandau Sub-district, whereas in Siak Hulu it is not yet running smoothly. Second, obstacles to exercising authority come from both superiors and subordinates. In Sungai Mandau, the Regent has no doubt about the sub-district head's capability and sees no problems with his performance. In Siak Hulu Sub-district, the Regent is concerned about the quality of his staff's work, while the sub-district head experiences difficulty in carrying out his tasks. Third, the implications of local-regulation implementation different: in Sungai Mandau the implications are positive, whereas in Siak Hulu they are less favorable. Fourth, with respect to sub-district performance over the past three years, Sungai Mandau has shown improvement, while Siak Hulu has remained flat. Fifth, the model used by the Regent to delegate authority to the sub-district head differs by regency: Siak employs the Rational-Comprehensive model, whereas Kampar uses the Incremental model. Keywords: Delegated; Authority; PATENT;